2017
DOI: 10.1088/1367-2630/aa60d4
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency thermal switch based on topological Josephson junctions

Abstract: We propose theoretically a thermal switch operating by the magnetic-flux controlled diffraction of phase-coherent heat currents in a thermally biased Josephson junction based on a two-dimensional topological insulator. For short junctions, the system shows a sharp switching behavior while for long junctions the switching is smooth. Physically, the switching arises from the Doppler shift of the superconducting condensate due to screening currents induced by a magnetic flux. We suggest a possible experimental re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 46 publications
0
45
0
Order By: Relevance
“…Recently, phase-coherent heat transport in superconducting circuits has been observed experimentally [15]. The possibility to control heat currents via magnetic fields has led to a number of proposals for phase-coherent caloritronic devices such as heat interferometers [16,17] and diffractors [18,19], thermal rectifiers [20][21][22][23], transistors [24,25], switches [26] and circulators [27], thermometers [28,29] as well as heat engines [30][31][32] and refrigerators [33,34]. Experimentally, heat interferometers [15,35,36], the quantum diffraction of heat [37], thermal diodes [38] and a thermal router [39] have been realized so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, phase-coherent heat transport in superconducting circuits has been observed experimentally [15]. The possibility to control heat currents via magnetic fields has led to a number of proposals for phase-coherent caloritronic devices such as heat interferometers [16,17] and diffractors [18,19], thermal rectifiers [20][21][22][23], transistors [24,25], switches [26] and circulators [27], thermometers [28,29] as well as heat engines [30][31][32] and refrigerators [33,34]. Experimentally, heat interferometers [15,35,36], the quantum diffraction of heat [37], thermal diodes [38] and a thermal router [39] have been realized so far.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the continuity of the wave function at the interfaces, we obtain the wave function in the central region, which provides direct access to the transmission probability of quasiparticles through the junction. We remark that while the normal state transmission of a 2D TI equals unity due to Klein tunneling preventing backscattering in the presence of time-reversal symmetry, the transmission in the superconducting state depends on energy, phase difference and magnetic flux in a nontrivial way, due to interference effects [56]. These quantum interferences also manifest themselves in the density of states of the junction.…”
Section: Model and Basic Definitionsmentioning
confidence: 87%
“…The rectification efficiency can be further increased by actively closing the quasiparticle gap only in the forward direction via the thermal switch effect proposed in Ref. [47]. In this case, R can reach values of up to 10 6 % for a temperature of the hot junction below the superconducting critical temperature as displayed in Fig.…”
Section: Thermal Rectification In Tsquiptmentioning
confidence: 90%
“…For example, in Ref. [47] it was shown that a topological Josephson junction subject to a magnetic flux can operate as a highly efficient thermal switch. The operational principle relies on the Doppler shift of the superconducting condensate which arises from screening currents that flow in response to the magnetic flux [83,84].…”
Section: High-efficiency Thermal Switchmentioning
confidence: 99%